Mental Rotation of Junior High School Students in Terms of Differences Sex - Ervi Anisatul Awalah; Mega T. Budiarto; Elly Matul Imah (International Journal of Trends in Mathematics Education Research, 2019)
Spatial ability has been recognized as a significant human skill involving the retrieval, retention, and transformation of visual information in a special context. One type of spatial ability is the skill of performing mental rotations. Mental rotation is is the ability to rotate two or three-dimensional objects rapidly and accurately in the mind. . In other words, by way of rotating objects mentally and thereby solving problems related to space, this test includes the limit of reaction time and the rotation angle, both of which are mutually related to the degree of difficulty. The subject of this research comes from 9th grades students at junior high school in Surabaya were selected from purposive sampling. The volunteer student with high ability in mental rotation based from differences gender were selected from mathematic ability task and interviewed. The result showed that high ability male students able to visualize the result of two-dimensional wake rotation such as right triangle rotated as 45°, 90°, 180° and 360. While high-ability female students are still somewhat difficult to visualize the result of two-dimensional rotational objects such as triangle too but had difficultness when rotated as 45°.